The Effect of Product Quality and Price Perception on Repurchase Intention Through Customer Satisfaction of Bata Shoes in Bandung Raya - MAOLANA, Mochammad Restu; MARLIANI, Leni Evangalista (PT Keberlanjutan Strategis Indonesia, 2025)
The purpose of this study is to investigate the relationship between Bata shoe quality, price perception, and repurchase intention in the Bandung Raya area, as mediated by customer satisfaction. Despite a positive growth trend in the national footwear market, the declining Top Brand Index for Bata shoes over the last three years suggests a decline in customer repurchase interest. A total of 120 respondents who had purchased or worn Bata shoes at least once in the past 12 months were given questionnaires as part of this study's quantitative survey methodology. The Sobel test and multiple regression were used to assess the mediating role and interpret the data. The results show that perceptions of product quality and pricing have a favourable and significant impact on both consumer satisfaction and repurchase intention. Additionally, it has been demonstrated that the relationship between repurchase intention and perceptions of price and product quality is mediated by customer satisfaction. PT Sepatu Bata Tbk's management will likely use these findings to create marketing plans that prioritise raising customer satisfaction, modifying price perception, and enhancing product quality to promote repurchase intention.